Perbandingan Teknik Zikir Tarekat dan Teknik CBT Sebagai Terapi Depresi (Studi Pemikiran al-Sya'ra>ni dalam al-Anwa>r al-Qudsiyah dan Teknik CBT Made Simple Nina Josefowitz) - Rosidi Rosidi; Ahmad Syatori (Program Pascasarjana UIN Sultan Maulana Hasanuddin Banten, Jalan Jenderal Sudirman No. 30, Serang - Banten 42118, 2023)
CBT (Cognitive Behavioral Therapy) techniques are widely applied in the treatment of depression sufferers, as well as dhikr is believed to have a therapeutic function in addition to other functions that are more popular. This study aims to compare the CBT technique Made Simple by Nina Josefowitz and the concept of remembrance by Imam al-Sya'rani in the book al Anwar al-Qudsiyyah regarding its function as a therapy for treating depression. Based on the results of analysis using inductive, content analysis and comparative methods, this study found similarities and differences in the concept of tarekat remembrance in the book al-Anwar al-Qudsiyyah with the CBT Made Simple technique as a treatment for depression. Among them is the optimization of both in terms of both relying on the quality of communication, but communication in mind orders tend to be more complex, formed between pupils and murshids continued to the sheikhs-sheikhs in the lineage of the order, to the Prophet of God Saw., until it reaches God, while communication in the CBT Made Simple technique is only formed between the client and the therapist who handles it. Thus the dhikr with a predetermined technique has more effect on people with depression compared to the CBT Made Simple technique, although in several ways this technique has advantages.